MODEL PEMBELAJARAN AL-QUR’AN PADA QUR’ANIC FUN CAMP DI PROBOLINGGO - Rahmah, Yohanida Arditia; Faridi; Nur Afifah Khurin Maknin (TADRIS: Jurnal Pendidikan Islam, 2021)
Al-Qur’an is Allah’s word. It contains guidance, conceptual basis, primary sources law and guidance of life for Muslims. The functionalization of the Qur’an requires the reader's ability to recognize letters, readings, language, and insight into the Qur'an. This study aims to determine the learning model of the Qur’an in the Quranic Fun Camp (QFC) program, which the Darussalam Gontor modern cottage family carries out in Probolinggo City. This research is a qualitative research with a descriptive approach. Collecting data using the technique of servation and interviews. The data analysis technique used a descriptive-exploratory model involving three analysis components: data reduction, data presentation, and concluding. This study's conclusions are: (1) QFC held al-Qur'an learning activities because they were worry about the tendency of some of the millennial generations spend much time on gadgets; (2) The learning model of the Qur'an in QFC did not initially use standard standardized methods, but in the end, it was decided to use the Qiro'ati method. Modern methods are also used to perfect this method, such as the game method, the demonstration method, and the drill method. ing the subsequent research